Hiking (Pendakian Gunung) dalam Perspektif Hadis: Studi Hadis Tematik - Rio Kurniawan; Endad Musaddad (Al-Hasyimi: Jurnal Ilmu Hadis, 2025)
Mountaineering is now a popular activity in Indonesia, but climbers' behavior that lacks environmental ethics often triggers natural damage such as water pollution, illegal logging, and scattered garbage. This study aims to examine the ethics of climbing from the perspective of hadith by emphasizing the concept of natural Hablum as a form of spiritual and ecological responsibility for humans. The research uses a qualitative method based on literature study through thematic analysis of primary and secondary literature, including the interpretation of the Qur'an and related hadiths. The results show that mountains in Islamic teachings have an important meaning as the earth's peg, source of water, and place of blessing, so maintaining its preservation is a moral obligation as well as worship. Climbers are encouraged to avoid destroying flora-fauna, polluting water sources, and littering, and are expected to have a spiritual-ecological awareness that reflects the balance of Hablum minallah, Hablum minannas, and Hablum minal nature.